2002
DOI: 10.1375/136905202320906363
|View full text |Cite
|
Sign up to set email alerts
|

Pittsburgh Registry of Infant Multiplets (PRIM)

Abstract: T his paper describes the Pittsburgh Registry of Infant Multiplets (PRIM; Pittsburgh, Pennsylvania), the results of pilot research conducted in this registry, and the plans for future studies. The main focus of the registry is on psychological development and the risk for behavioral disorders. Particularly, characteristics associated with antisociality and the risk for substance use disorders (e.g., aggressivity, hyperactivity/impulsivity), as well as language development and other traits (e.g., dental health)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The algorithm for determining zygosity has been described elsewhere. 41 It has been previously demonstrated that this short questionnaire has an accuracy of 94% for zygosity determination when compared with molecular genetic results [41,42]. All aspects of this study were approved by an Institutional Review Board (IRB).…”
Section: Methodsmentioning
confidence: 99%
“…The algorithm for determining zygosity has been described elsewhere. 41 It has been previously demonstrated that this short questionnaire has an accuracy of 94% for zygosity determination when compared with molecular genetic results [41,42]. All aspects of this study were approved by an Institutional Review Board (IRB).…”
Section: Methodsmentioning
confidence: 99%
“…Each family member independently completed anonymous paper-and-pencil questionnaires. A brief zygosity questionnaire developed by Nichols and Bilbro (1966), with the corresponding zygosity determination algorithm developed by Eley and colleagues for the Twins Early Development Study (TEDS) in London [personal communication (Strassberg et al 2002; Jenkins et al 2006)] was used for zygosity determination. The questionnaire is composed of 15 items to evaluate the similarity and differences between members of the twin pair.…”
Section: Methodsmentioning
confidence: 99%
“…Most volunteer-based registers rely on advertising to recruit participants, and this is achieved using various media outlets, referrals by health professionals, and contact through twins clubs, parishes, schools and hospitals (Baker et al, 2002;Boomsma et al, 2002b;Hayakawa et al, 2002;Hopper, 2002;Jang et al, 2002;Spector & MacGregor, 2002;Spinath et al, 2002;Strassberg et al, 2002).…”
mentioning
confidence: 99%